Optimization of a coupled vane compressor - Lim, Zhi Jun (2019)
The compressor has been widely used in many industries in recent years, especially in the air compressor, heating and refrigeration industries. There are plenty of different types of rotary compressor out there in the market such as the sliding vane compressor, the rolling piston compressor, the rotary screw compressor and the scroll compressor. With such a wide range of compressors in the market, it is important for a novel compressor to be efficient. This project aims to find the optimal design variables that optimise the mechanical efficiency of a novel compressor, Coupled Vane Compressor (CVC). The optimisation study was done by coupling the mathematical model of CVC and the optimization algorithm in a simulation program using the FORTRAN programming language. In this project, the complex optimisation method is chosen which is a direct search, multi-variable and constrained optimisation method. After the optimisation study, it was found that the cylinder radius was reduced by 14.98 % while the rotor radius has an increment of 26.91 % from the original design value. Furthermore, the vane length was reduced by 52.34 % and the height of the cylinder was found to have an increment of 555.95 % from the original design value. The changes in these design values lead to a 32.3 % decrease in total power loss. Thus, the mechanical efficiency of the optimised design values increased by 5.43 % compared to the original design value.